Investigating Cohesiveness of QS. Al-Mā’idah: A Review on Michel Cuypers Implementation of Semitic Rhetorical Analysis (SRA) - Aqdi Rofiq Asnawi; Husein Aziz; Achmad Murtafi Haris (UIN Sunan Kalijaga Yogyakarta, 2022)
This article examines Michel Cuyper’s interpretation of the Qur’an which is the result of the application of Semitic Rhetorical Analysis (SRA) in QS. Al-Mā’idah. Although SRA’s implementation has demonstrated the coherence of the Qur’anic text; however, no one has properly articulated the cohesiveness of the Qur’anic text as the basis of that coherence. Thus, to ascertain the text’s cohesiveness in terms of positions and forms from the SRA’s perspective, this study applied cohesion text theories to Cuypers’ implementation of SRA in QS. Al-Mā’idah. A thesis of the paper is that, according to SRA, the cohesiveness of a qur’anic text in QS Al-Mā’idah can be shown through the pairings of words or sentences inside particular groupings of text particles following the principles of Semitic Rhetoric. The Semitic Rhetoric’s principle of parallel, concentric, or mirror symmetry in those text particle groups determined which words or phrases are paired in a text particle group. As a result, from an SRA perspective, the Qur’anic text’s cohesiveness may be discovered at each level of the text particle group, demonstrating multi-layered cohesiveness. In Cuypers’ reading of QS Al-Mā’idah, synonyms and repetition are used to maintain lexical cohesion, while ellipsis, substitution, and reference established grammatical cohesion.